Harnessing diversity from ecosystems to crops to genes. (February 2017) - Buchanan‐Wollaston, Vicky; Wilson, Zoe; Tardieu, François; Beynon, Jim; Denby, Katherine
Abstract: To feed humanity, while maintaining a stable and diverse biosphere, crop science needs to adapt to an open research environment where genetic resources and the data demonstrating the environments in which they are effective are freely shared. The challenge faced is to expand crop production on a reduced land area, due to environmental degradation caused by human encroachment and climate change, while maintaining biodiversity. Individual researchers are discovering alleles and genetic combinations that are effective in certain environments but not in others. These data and alleles are useful globally to speed progress in breeding for similar environments while not wasting time on ineffective genotypes. However, currently, there are significant barriers to the sharing of genetic resources and their underpinning data, which must be overcome if we are to sustain the planet for future generations. Abstract : This review highlights the importance of understanding, sharing and exploiting biological variation to drive sustainable agriculture which includes diversity of agroecosystems, crop species and varietal genetics. We discuss the importance of open data, enhanced data accessibility and annotation, as well as innovation in methods for analysis and reuse of data which are essential to capitalise on crop stress resilience research. The Global Plant Council could play a vital role in driving global approaches to facilitate the use of diversity and data to enhance crop stress resilience. Specific actions are outlined in the paper.